Verbal memory depends on structural hippocampal subfield volume - Tsalouchidou, Panagiota-Eleni; Müller, Christina-Julia; Belke, Marcus; Zahnert, Felix; Menzler, Katja; Trinka, Eugen; Knake, Susanne; Thomschewski, Aljoscha (Frontiers in Neurology, 2023)
Objective To investigate correlates in hippocampal subfield volume and verbal and visual memory function in patients with temporal lobe epilepsy (TLE), mild amnestic cognitive impairment (MCI) and heathy participants (HP). Methods 50 right-handed participants were included in this study; 11 patients with temporal lobe epilepsy (TLE), 18 patients with mild amnestic cognitive impairment (MCI) and 21 healthy participants (HP). Verbal memory performance was evaluated via the verbal memory test (VLMT) and visual memory performance via the diagnosticum for cerebral damage (DCM). Hippocampal subfield volumes of T1-weighted Magnetic Resonance Imaging (MRI) scans were computed with FreeSurfer version 7.1. Stepwise correlation analyses were performed between the left hippocampal subfield volumes and learning, free recall, consolidation and recognition performance scores of the VLMT as well as between right hippocampal subfield volumes and visual memory performance. Results The volume of the left subicular complex was highly correlated to learning performance (β = 0.284; p = 0.042) and free recall performance in the VLMT (β = 0.434; p = 0.001). The volume of the left CA3 subfield showed a significant correlation to the consolidation performance in the VLMT (β = 0.378; p = 0.006) and recognition performance in the VLMT (β = 0.290; p = 0.037). There was no significant correlation identified between the right hippocampal subfields and the visual memory performance. Conclusion The results of this study show verbal memory correlates with hippocampal subfields and support the role of left subiculum and left CA2/CA3 in verbal memory performance.